2018
DOI: 10.1111/cfs.12614
|View full text |Cite
|
Sign up to set email alerts
|

Young carers in Sweden—A pilot study of care activities, view of caring, and psychological well‐being

Abstract: Children who have parents with any kind of illness may become young carers who take a responsibility not expected of children for household tasks, or personal or emotional care for parents and siblings. So far, little is known about children in Sweden who are at risk of becoming young carers. The aim of this article is therefore to explore the extent and impact of children's caring activities as reported in a pilot study by a sample of children in Sweden. A number of international questionnaires measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 21 publications
4
36
1
Order By: Relevance
“…This makes it useful for assessment purposes when used by social workers and health professionals. It has been increasingly used as a survey instrument across different cultures, including the United Kingdom (e.g., Becker and Sempik 2018), Sweden (e.g., Järkestig-Berggren et al 2018), and Switzerland (e.g., .…”
Section: Ethics Of Developing the Quality Of Methodologymentioning
confidence: 99%
“…This makes it useful for assessment purposes when used by social workers and health professionals. It has been increasingly used as a survey instrument across different cultures, including the United Kingdom (e.g., Becker and Sempik 2018), Sweden (e.g., Järkestig-Berggren et al 2018), and Switzerland (e.g., .…”
Section: Ethics Of Developing the Quality Of Methodologymentioning
confidence: 99%
“…It consists of two 10-item subscales (positive and negative outcomes) with adequate internal consistency and expected associations with depressive symptoms [ 105 ]. A Swedish adaptation has been used in previous studies, showing adequate internal consistency [ 6 ]. Finally, perceived social support will be measured using an adapted version of the brief social support questionnaire (SSQ-6) [ 106 ] that includes 3 items asking to indicate the number of support sources and one item asking for global satisfaction with received social support (6-point scale ranging from very dissatisfied to very satisfied), and one multiple-choice ad-hoc question on individuals (i.e., school staff, close family members and close friends) AYCs can count on if in need of support or help.…”
Section: Original Study Protocol Methodsmentioning
confidence: 99%
“…Taking on care responsibilities early in life may have considerable negative consequences for young people’s mental and physical health and psychosocial development [ 4 , 5 , 6 , 7 , 8 , 9 ]. Caring has especially been linked to stress, anxiety and depression symptoms when occurring in the adolescent phase [ 10 , 11 ], which is remarkable given evidence that most mental health problems that start during adolescence subsequently persist into adulthood [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Gould (1995) showed that few people thought it was likely that children with physically disabled parents would be young carers because of the available resources for this group of parents. However, studies show that young carers do exist and that their problems are not always addressed (Gould 1995;Järkestig Berggren et al 2018;Kallander et al 2018aKallander et al , 2018bNordenfors, Melander, and Daneback 2014).…”
Section: Parental Care Societal Responsibility and The Rights Of Thementioning
confidence: 99%